Part of the primula collection at the at the Arctic and Alpine Botanic Garden in Tromsø, Norway ... - Campbell, Sandy (University of Alberta Library, 2024)
View of part of the primula collection planted on a rocky outcrop at the Arctic and Alpine Botanic Garden (latitude 69.6769° N) in Tromsø, Norway blooming in early June, 2024. Varieties visible include Primula angustifolia and Primula lutea. ...